Wpływ Warunków Początkowych na Drgania Swobodne Pręta Zamocowanego Nieliniowo - Cempel, C. (Engineering Transactions, 1969)
This paper is devoted to the analysis of the influence of the initial conditions on the frequency of nonlinear vibrations. Making use of Weyl's theorem on the mean value relations are obtained for the frequency of vibration of any order. By considering a numerical example it is shown that the initial velocity can be disregarded only oif the velcity amplitude is of the order of the static deflection of the bar.